Fatores associados ao binge drinking, beber frequente ou pesado e primeiro uso de álcool entre adolescentes brasileiros - Conegundes, Lara Silvia Oliveira [UNIFESP] (2017)
Harmful alcoholic beverage consumption by adolescents constitutes a world public health issue. It is important to detect and understand the main factors driving adolescents on the pathway of drinking and alcohol abuse. Preventive programs are required to bar excess alcohol consumption or delay as much as possible this habit. The aim of this study was to understand the relationship between demographic, social and family factors associated with binge drinking (BD), heavy drinking (HD) or frequent drinking (FD) and the beginning of alcoholic beverage consumption or the beginning of BD. The impact of the preventive program #Tamojunto (We’re together buddy) was assessed. A randomized controlled study was conducted in 72 public schools to investigate Junior High and High School students in six Brazilian cities. The intervention group schools went through the #Tamojunto program and the control schools did not go through any preventive drug use program. Data were collected in anonymous surveys at baseline, 9 and 21 months after baseline, using self-completed questionnaire forms. In the first paper baseline cross-sectional data were assessed for the association between annual BD and monthly HD or FD and demographic, family and social factors (N=6,387). In the second paper, only the baseline non-drinking students were assessed (N=2,649) in this longitudinal segment. The factors associated with the beginning of alcohol use and binge drinking in this group and the effect of the program on the outcome were assessed. Logistic weighted regression models with school variance adjustments were used. Average age at baseline was 12.6 years and 16.5% of the respondents reported BD and 2.2% HD/FD. Potential factors associated with BD were: older age, tobacco, marijuana and inhalant use, average to low school scores, verbal aggression, bullying exposure, and exposure to a drunkard in the family. At the end of the study 49.7% non-drinkers reported to have started using alcohol and 16% to have started BD. The intervention group presented an increased chance of trying alcohol among students who did not live with their mother, when compared to the control group. The predictors of the first alcohol experience were: parents’ occasional alcoholic beverage use, father not living with the family, be part of a more privileged social class, female gender, average and low school scores and physical aggression in school. The predictors of the initiation of BD practice were exposure to a drunken mother, to father or best friend’s sporadic alcohol use, female gender, older age, average and low school scores, verbal aggression and bullying. The results of this study clearly indicated the need for an efficient preventive program, that, unlike the #Tamojunto program reduces initiation of the use of alcohol. The trials established an association between aggressive behavior, poor school performance and more privileged social class. Alcoholic parents and friends’ alcohol consumption may be risk factors, including sporadic drinking.